2011
DOI: 10.1039/c1ee01405f
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual thermal actuation system driven by interface tension of nanofluids

Abstract: In a system containing nanoporous materials and liquids, the well-known thermo-capillary effect can be amplified by the ultralarge specific surface area of the nanopores. With appropriate temperature change, the relative wetting-dewetting transition can cause the liquid to flow in or out of the nanopores, and part of the thermal energy is converted to significant mechanical output. A conceptual design of such a thermal actuation/energy conversion/storage system is investigated in this paper, whose working mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…A lthough Eq. (1) may not be valid for nanochannels, it has been reported that the pressure needed to drive w ater into carbon nanotubes (CN Ts) at room tem perature ranges from around 50 to 300 MPa, depending on the size o f CN Ts [11][12][13]. For nanoporous zeolite with pore size of about 1 nm, the infiltration pressure o f w ater at room tem perature is about 8 0 -1 5 0 M Pa [14,15].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A lthough Eq. (1) may not be valid for nanochannels, it has been reported that the pressure needed to drive w ater into carbon nanotubes (CN Ts) at room tem perature ranges from around 50 to 300 MPa, depending on the size o f CN Ts [11][12][13]. For nanoporous zeolite with pore size of about 1 nm, the infiltration pressure o f w ater at room tem perature is about 8 0 -1 5 0 M Pa [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…Both com puted and m easured infiltration pressures are higher than the predictions o f Eq. (1) ' mezli@ust.hk [11][12][13][14][15][16][17][18], O ther than the w ork in Refs. [1 1 -1 5 ], experim ents on w ater infiltration into nanoscale hydrophobic silica pores show that the infiltration pressures are about 1.5-2 tim es higher than the Young-Laplace equation [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar difference of intrusion and extrusion curves can be seen on PV-diagrams at room temperature obtained by Patarin and co-workers 12 . The properties and characteristics determined for the investigated {ZIF-8 + water} molecular spring may be extended to numerous applications in the field of mechanical and thermal energy storage as well as for thermal to mechanical energy transformation 1,2,19 . Previously non-observed simultaneous and reversible effect of temperature and pressure on porosity of ZIF-8 ( Fig.1) is important for MOF applications 14 .…”
mentioning
confidence: 99%
“…That thermal and electrical stimuli may serve as an additional way to control nanofluids to make the system highly responsive to multiple external fields deserves note. 20,21 Moreover, use of nanoribbons and graphene sheets in NRCs also permits the utilization of the remarkable mechanical, thermal, and electronic properties of these materials to create highly multifunctional systems. Normalized density profile, axial velocity profile, standard deviation of axial velocity, and in-plane velocity profile along the y-direction (thickness direction, vertical) for the steady-state transport of water through four NRCs at 50 m s À1 .…”
mentioning
confidence: 99%